African Customary Dispute Resolution vs Alternative Dispute Resolution for Juvenile Crime in Ghana - Hassan, Elizabeth (Journal of Law, Society and Development, 2022)
Juvenile delinquency is a challenge for most African states, and Ghana is no exception. Recidivism, stigmatisation and victim dissatisfaction indicate that Ghana’s formal criminal justice system, with all its merits, has posed severe challenges to the administration of juvenile justice. This article examines the practice of Alternative Dispute Resolution (ADR), which utilises restorative conflict resolution processes in place of prosecution and sentencing in juvenile justice systems of various jurisdictions. Through processes such as victim-offender mediation, ADR invites full participation and consensus between victims, offenders and persons indirectly affected by the crime committed and seeks full and direct accountability. Some inadequacies of ADR principles and practices render it less relevant to the African context. The resultant lacuna can be filled with indigenous dispute resolution practices to combat crime and its repercussions, constituting the African Dispute Resolution (AfDR). The reliance on Ubuntu in South Africa's Child Justice Act and traditional justice system mechanisms in the Democratic Republic of Congo, Rwanda and Uganda to deal with the aftermath of genocides and wars are contemporary examples of AfDR. Ghana would need to rely on AfDR to complement its formal criminal justice system to alleviate juvenile delinquency.